Rational design of carbon-based materials for purification and storage of energy carrier gases of methane and hydrogen - Mirzaei, Shohreh; Ahmadpour, Ali; Shao, Zongping; Arami-Niya, Arash
Today, fast-growing energy demands and fuel resource depletion are among the hottest concerning issues that treating our world. So, a huge need is felt to find efficient, affordable and eco-friendly energy storage and production systems. Much current research effort proved that gaseous energy carriers such as CH4 and H2 seem to be the right choice for alternative fuel resources. However, the most important challenge with this new-faced resource is the comparatively low volumetric energy storage density. Fortunately, the high-pressure gas storage technique inside the porous media of solid adsorbent is considered as one best way to tackle the energy density problem. Famous family of porous carbon materials, with a suitable pore size distribution centred in the micropore range and a large number of adsorption sites per volume of solid, open up a great scope for gas storing applications. This review article represents the state-of-the-art with a precise focus on what has and can be done to improve/enhance the gas/energy storage capacity of traditional and novel structures of low-cost carbon-based adsorbents. We review a wide variety of design strategies to synthesis carbonaceous adsorbents, with a strong focus on creating the connection between structural properties and gas adsorption performance. In this regard, various synthesis techniques have been studied with emphasis on the more interesting recent progress that allows better control and optimisation of porosity of porous carbons for maxing gas storage capacity. We will also show that carbon-based adsorbents, particularly activated carbons, have been extensively studied and remain a powerful candidate in the search for an energy carrier economy. In the end, a perspective is provided to forecast the future development of carbon-based materials.